2012
DOI: 10.1155/2012/282784
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Extramedullary Plasmacytoma of the Thyroid Gland

Abstract: Solitary extramedullary plasmacytoma of the thyroid gland is an uncommon condition. Up to date, its clinical pathological features are not fully understood. We present a case of an extramedullary nonmucosal plasmacytoma of the thyroid gland which is the first case with regional metastatic lymph nodes. This condition requires a scrupulous survey to rule out a metastatic multiple myeloma. Although localized forms management is still controversial, authors require combined approach for regional metastatic forms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…Lymphocytic thyroiditis is usually accompanies EMP of thyroid gland [4] however, some studies have not found any association between lymphocytic thyroiditis and EMP. [10] In our case; we did not find any histological features of underlying lymphocytic thyroiditis. Common histological mimickers of EMP thyroid include medullary carcinoma of thyroid [11] and lymphoplasmacytic lymphoma.…”
Section: Discussioncontrasting
confidence: 42%
“…Lymphocytic thyroiditis is usually accompanies EMP of thyroid gland [4] however, some studies have not found any association between lymphocytic thyroiditis and EMP. [10] In our case; we did not find any histological features of underlying lymphocytic thyroiditis. Common histological mimickers of EMP thyroid include medullary carcinoma of thyroid [11] and lymphoplasmacytic lymphoma.…”
Section: Discussioncontrasting
confidence: 42%
“…Similarly Ridal et al . [ 9 ] diagnosed a case of EMP as lymphoplasmacytic lymphoma on cytology. Sarin et al .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of EMP remains controversial; all three modalities, including radiotherapy alone, surgery alone, or a combined approach, are advocated by various authors [ 11 ]. Although EMP is very sensitive to radiotherapy and complete remission can be achieved by irradiation alone in most cases, surgery remains the treatment of choice if the tumor is resectable.…”
Section: Discussionmentioning
confidence: 99%
“…The patient has been followed up regularly in the surgical OPD for the last eight months and has remained asymptomatic to date. Long-term follow-up of EMP is advised, as around 20% cases of EMP may progress to MM [ 11 ].…”
Section: Discussionmentioning
confidence: 99%